Cytokeratin 8,18 and 19 expressions, epithelial shedding, and stromal extravasation in endometrium of norethisterone enanthate (NET-EN) progestogen contraceptive users (A preliminary report) (Faculty of Medicine Universitas Indonesia, 1998)
[no abstract available]